Incidentes relacionados a medicamentos em uma instituição hospitalar: subsídios para a gestão - D' Aquino, Flavia Fernanda Rosa [UNESP] (2014)
The patient safety is the key to assure the quality of care assistance. The nurse manager for its function has the ability to identify gaps in drugs preparation and administration and with the help of other professionals to know the flaws in the whole system of medication and together to search for safety in drug therapy. The aim of this study was to identify drug-related incidents and the determinant factors in the notifications sent to the Center for Patient Safety in a public hospital in the state of São Paulo. Descriptive, transversal, retrospective study with quantitative approach. The incidents were identified from 189 spontaneous notifications submitted to the Center for Patient Safety of that institution from June, 2011 to June, 2012. The most reported incidents were medication errors (61.5 %), in Clinical Unit (25.9 %) and Pediatrics (18.5 %); in the dispensation step, wrong dispensation category (48.3%) and wrong patient (13.8%). The most involved drugs in the notifications were antibiotics (19.0%) and intravenous solutions and their additives (16.4%). Hight-Alert Medications were 54.3 % of the medications. Of total incidents, 19.8 % did not cause any harm to patients, 8.6% were related to damage (adverse event) and 60.4 % of them were intercepted by nurses before reaching a patient (near miss). The results of this study provide sources to the professionals involved in the medication system to implement strategies to prevent incidents. An educational booklet about the culture of patient safety was developed as a result of this study to encourage spontaneous notifications, concepts and strategies for prevention